Discouragement effect and alternative formats to increase suspense in professional biathlon - Krumer, A. (Molde University College, 2020)
Research Question: The paper analyzes mass start competitions in professional biathlon to identify the existence of discouragement effect, according to which biathletes reduce their efforts when lagging far behind the leaders. Research Methods: We use data on all 148 mass start competitions, for both genders, in World Cups, World Championships, and Olympic Games from 2001/02 to 2016/17 seasons, and compare the gap times between the two consecutive ranks. Results and Findings: We find that the 95% confidence intervals of the gap times between the two consecutive ranks overlap in the range of rankings between 3 and 25 among men and between 5 and 24 among women,with mean gaps of 6.6 and 7.6 seconds among men and women,respectively. However, that gap increases sharply for the four bottom ranks,with mean gaps of 31.6 and 33.1 seconds among men and women,respectively.Implications: The results of this study suggest that bottom-ranked biathletes strategically reduce their efforts when there is nothing at stake. Such a strategy increases the duration of television broadcasts and does not help maximize suspense, which is one of the main drivers of television demands in professional sports. We offer an alternative format according to which a certain number of the bottom-ranked biathletes will be eliminated after each bout of shooting. Such a format should dramatically increase the suspense-to-time ratio.